Perlindungan Hukum terhadap Hak Merek pada Merchandise GMMTV yang Belum Terdaftar di Indonesia - Nuraeni, Een; Ayodhya, Devika Tryza (Institut Agama Islam Nasional Laa Roiba Bogor, 2026)
Legal protection for well-known foreign brands that have not been registered in Indonesia is an important issue considering that Indonesia adopts a first-to-file trademark registration system. This system has the potential to harm owners of well-known foreign brands if another party registers the brand in bad faith. This study aims to analyze the legal regulations and forms of legal protection for well-known foreign brands that have not been registered in Indonesia with a case study of the GMMTV brand. The research method used is normative legal research with a statutory approach and a conceptual approach, using primary and secondary legal materials. The results of the study indicate that although trademark protection is in principle provided through registration, Law Number 20 of 2016 concerning Trademarks and Geographical Indications provides special protection for well-known brands that have not been registered through the mechanism of registration rejection, cancellation lawsuit, and civil lawsuit based on bad faith. This protection is also strengthened by the provisions of the Paris Convention and the TRIPs Agreement, which Indonesia has ratified. In the context of GMMTV, the brand meets the criteria for a well-known foreign trademark due to its international reputation and widespread recognition in Indonesia, and therefore still enjoys legal protection even though it is not yet registered. Therefore, the national and international legal framework in Indonesia provides an adequate basis for protection for well-known foreign trademarks to prevent unfair business competition and consumer misuse.